Performance Analysis of a Two-Stage Savonius Rotor Using Numerical Methods - Aziz, Abdul; Rama, Hilfama; Al-Huda, M. Firash; Zahndi, Mirwan; Sumiati, Ruzita (Program Studi Teknik Mesin Universitas Pamulang, 2026)
The POCREN system is a hybrid renewable energy device that integrates wind, solar, and water current energy sources to generate electrical power. The main objective of developing POCREN is to provide a sustainable electricity supply, particularly for floating fish farmers in coastal regions where the average wind speed ranges from 3 to 5 m/s. Currently, most floating cage farmers rely heavily on diesel engines to meet their electricity needs, which are costly and environmentally unsustainable. This study focuses on one of the key components of the POCREN system, namely a two-stage Savonius wind turbine, to evaluate its performance in power generation. The analysis was conducted numerically using ANSYS Fluent software. The results show that the maximum power coefficient (Cp) of the two-stage turbine was achieved at a wind speed of 5 m/s with a tip speed ratio (TSR) of 0.7, yielding a Cp value of 0.26. At a lower wind speed of 3 m/s, the maximum Cp reached 0.22 at the same TSR of 0.7. Pressure contour analysis indicates that the two-stage Savonius turbine can operate effectively at low wind speeds of approximately 3 m/s. The pressure distribution shows higher pressure on the concave side of the advancing blade compared to the convex side, generating torque that drives rotor rotation. This confirms that the two-stage configuration enhances torque continuity and enables stable operation under low wind conditions. Based on these findings, the two-stage Savonius turbine in the POCREN system is suitable for renewable energy applications in coastal environments, offering a promising alternative to reduce dependence on diesel-powered generators for floating fish farming activities.